Development and in-vitro, in-vivo evaluation of Pioglitazone-loaded polymeric nanoparticles using central composite design surface response methodology - Dinesh Kumar Sharma; Gurudutta Pattnaik; Amulyaratna Behera (OpenNano, 2023)
Pioglitazone is a type 2 diabetes drug encapsulated in polymeric nanoparticles using solvent evaporation techniques. In this study, the drug-polymer ratio (A), stirring speed (B), and stirring time (C) were three process parameters that were optimized using a three-factor, three-level Central Composite design. Entrapment efficiency, Pioglitazone content, and particle size were assessed as responses to the three dependent variables. The independent and dependent variables were associated using mathematical equations and response surface graphs. The optimization model of entrapment efficiency of about 61.7 %, Pioglitazone content of 12.33 %, and particle size of 323 nm with A, B, and C levels of 1:2, 3000 rpm, and 20 min respectively. The expected values of the optimized technique and the observed responses exhibited good agreement. Morphological examinations, Fourier transforms infrared spectroscopy, and in-vitro drug release tests were used to characterize the produced nanoparticle. The synthesized nanoparticles demonstrated effective sustained drug release. In an in vivo system, the synthesized nanoparticles demonstrated enhanced drug bioavailability. Pioglitazone-loaded nanoparticle treatment of streptozotocin-induced diabetic rats significantly decreased blood glucose levels (up to 7 days) to normal levels (up to 6 hours) when compared to the native drug-treated group. The in vivo toxicity study of the nanoparticles in albino rats failed to detect any appreciable alterations in hematological, biochemical, or behavioral tests. Since Pioglitazone is used to treat type 2 diabetes mellitus, the created system may help achieve a regulated release of the medication, which could assist in lowering dosage frequency and improve patient compliance.